Development of Co-Crystallization Technique to Improve Solubility of Anti-Diabetic Drug - Burkhande, Ninad S.; Wankhade, V. P.; Atram, S. C.; Bobade, N. N.; Pande, S. D. (Asian Journal of Pharmaceutical Research and Development, 2023)
Co-crystallization is a useful crystal engineering approach for changing the physiochemical and structural characteristics of drug crystals. Pharmaceutical co-crystals are nonionic supramolecular complexes that can be utilized in pharmaceutical development to change physiochemical qualities including solubility, stability, and bioavailability without changing the chemical makeup of API. Canagliflozin Hemihydrate is a anti-diabetic drug. Canagliflozin belongs to class IV drug in BCS classification. i.e. low solubility and low permeability. The major problem of this class drug is it slow solubility in biological fluids,which results into poor bioavailability after oral administration. The purpose of this study was to prepare pharmaceutical co-crystals ofCanagliflozin to enhance solubility and dissolution rate by using co-crystallization technique. The co-former used inthis study is Thiourea. The Optimized co-crystal was characterized by FTIR, XRPD, SEM and other pharmaceutical properties like solubility and melting point were alsoevaluated.